Pengujian Digital Marketing, Price Perception dan Product Quality Guna Peningkatan Penjualan Oma Jamu - Annisah Febriana; Ratih Dewi Titisari Haryana (Fakultas Ekonomi Universitas Yos Soedarso, 2024)
The developments of information technology encourage UMKM players to be able to continue to keep up with current developments, especially in digital world. The aim of this research is to find out whether the use of information technology in the form of digital marketing is able to increase sales volume in one of the UMKM which is currently growing quite rapidly in Surabaya, East Java. Apart from that, this research also aims to determine price perception and product quality on sales volume at Oma Jamu. The analysis method uses multiple linear regression with sampling using non-probability sampling techniques where 85 respondents were obtained. The research results concluded that digital marketing, price perception and product quality have a significant influence on sales volume at Oma Jamu. These results show that it is important for every UMKM business actor to utilize information technology to develop their business network which is also supported by the perception of price and product quality required by consumers.